SISTEM PERTAHANAN ISRAEL DALAM MENGHADAPI PERKEMBANGAN KEAMANAN NASIONAL - Imanuel, Josafath; Sudirman, Arfin; Hakiki, Falhan (BHUVANA: Journal of Global Studies, 2024)
Israel was founded on May 14, 1948, with a declaration made by David Ben-Gurion. Since its founding, Israel has often faced external threats from other countries, such as Egypt and Jordan. As time goes by, Israel manages to reach peace agreements with its neighboring countries. It turns out that the external threats does not stop. Now, Israel needs to face threats from non-state actors such as Hamas and Hezbollah. Apart from that, developments in international relations have impacted the strategies for achieving national security. This research employs two theories: National Security with three key concepts and Civil-Military Relations with three key concepts. The research utilizes a qualitative method, including literature studies and internet-based research for data collection. This research aims to identify Israel's civil-military relations in facing non-traditional threats to ensure its national security. The results indicate that civil-military relations in Israel, integrated into the democratic system model, have successfully adapted to developments in national security. However, based on the findings of this research, there is no Israeli document in the form of a Defense White Paper serving as a basic constitution for dialogue between the government and the Israel Defense Force (IDF).